2016
DOI: 10.1021/acs.macromol.6b00268
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Evaluation of PP/PS Blends Filled with Different Types of Clays by Nonlinear Rheological Analysis

Abstract: The effects of various Cloisite nanoparticulate clays with different hydrophobicities on (80/20) polypropylene/polystyrene (PP/PS) blends were investigated using their linear and nonlinear rheological properties. In descending order of hydrophobicity the four Cloisite clays examined were C20A > C10A > C30B > CNa+. Clays with a wetting coefficient ω a of between 1 and −1, that is C20A and C10A, located at PP/PS polymer interfaces and suppressed coalescence, while clays with a ω a of >1, that is C30B and CNa+,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 44 publications
1
47
0
Order By: Relevance
“…As a result, the rheological properties of the blend changed slightly, most likely because of the hydrodynamic (volumetric) effects of particles rather than them acting as morphology modifiers. Salehiyan et al . reported similar results when hydrophilic particles (Cloisite30B, untreated CNa + clays, and OX50 fumed silica) were added to 80/20 PP/PS blends: they mostly localized inside the PS droplets.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…As a result, the rheological properties of the blend changed slightly, most likely because of the hydrodynamic (volumetric) effects of particles rather than them acting as morphology modifiers. Salehiyan et al . reported similar results when hydrophilic particles (Cloisite30B, untreated CNa + clays, and OX50 fumed silica) were added to 80/20 PP/PS blends: they mostly localized inside the PS droplets.…”
Section: Resultsmentioning
confidence: 64%
“…As a result, the rheological properties of the blend changed slightly, most likely because of the hydrodynamic (volumetric) effects of particles rather than them acting as morphology modifiers. Salehiyan et al 38,42,43 reported similar results when hydrophilic particles (Cloisite30B, untreated CNa 1 clays, and OX50 fumed silica) were added to 80/20 PP/PS blends: they mostly localized inside the PS droplets. In the case of BA80 OS2, particles went into both matrices in clusters and increased the viscosities of the polymers, that is, the viscosity ratios of the polymers may not have been disturbed enough to promote droplet breakup.…”
Section: Rheological Analysismentioning
confidence: 72%
“…In order to improve the properties of PP, a lot of inorganic fillers and rigid polymers have been used to prepare modified PP composites or blends 4‐7 . As a kind of rigid polymer, PS, with low cost, has been widely used for modifying PP to prepare PP/PS bends or its composites in recent years 8 . There are a lot of waste plastic products prepared from PP or PS every year.…”
Section: Introductionmentioning
confidence: 99%
“…Because very few molecular chains connect the two phases by traversing the interphase, the PP/PS blends usually result in serious phase separation with poor interfacial adhesion 11‐13 . Therefore, a lot of attempts have been carried out to improve the interfacial compatibility between the two phases of PP/PS blends 8,14‐21 . A number of compatibilizing agents have been applied to promote the adhesion between the PP and PS phases, such as PS‐ block ‐poly(ethylene‐butylene)‐ block ‐PS (SEBS) copolymers, 17 PP‐ g ‐PS graft copolymers, 18 and nanoparticles 8,19‐21 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that clays can be used as a different class of compatibilizer, as they can stabilize the blend morphology more specifically when they are located at the interface between the two phases. In addition, they can prevent coalescence of the minor phase domains . Consequently, finer morphologies yield superior properties, as the domain phase is well distributed throughout the matrix.…”
Section: Introductionmentioning
confidence: 99%